The Bhopal saga : causes and consequences of the world's largest industrial disaster - Eckerman, Ingrid (Universities Press, 2005)
The Bhopal Saga is an incisive analysis of the one of the worst industrial accidents that has taken place in the recent past. On the night of December 2 1984, while Bhopal slept, 43 tonnes of methylisocyanate and other substances leaked from the Union Carbide factory located in the city. By next morning the place was a graveyard of dead humans and animals. Of the 520,000 people who were exposed to the gases 8,000 died during the first week and 8,000 later. The impact on the survivors are visible even today. The pesticide plant from where the gas leaked was half-owned by the multinational Union Carbide and half by the Government of India. This book contains a thorough review of most of what has been written about the incident since 1984. It discusses the conflicting stance of the Union Carbide Corporation and the Governments of India on the moral responsibility for the tragedy. Using the “Logical Framework Approach”, Eckerman analyses the disaster. The analysis demonstrates that the two most important factors leading to the mega-gas leak were the design of the plant and the company policy of cutting back on expenses. The same analysis shows that negligence by the company and the authorities have critically affected the impact of the leakage on people’s lives.